Structural transformation of Ag3PO4 and Ag3PO4/TiO2 induced by visible light and Cl- ions: its impact on their photocatalytic, antimicrobial, and antifungal performance - Badurova, Katarina; Motola, Martin; Janczura, Adriana; Roch, Tomas; Satrapinskyy, Leonid; Gregus, Jan; Dworniczek, Ewa; Plesch, Gustav (Springer, 2020)
In this work, synthesis of Ag3PO4 and its composite with TiO2 (Ag3PO4/TiO2) toward study of two phenomena naturally occurring in Ag3PO4 is reported, specifically a visible light-driven (i.e., photocorrosion) and chloride ion-driven transformation of Ag3PO4 to AgCl in chloride-free and chloride-present aqueous solution. A deeper insight on this transformation via study of their structural and morphological changes using X-ray diffractometry (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS) is performed. Substantial amount of AgCl is detected in both Ag3PO4-based materials after visible light irradiation in chloride-present environment. This led to an increase in optical band gap of Ag3PO4 and Ag3PO4/TiO2 from 2.52 to 2.99 eV and 2.48 to 3.02 eV, respectively. Impact of these structural changes in Ag3PO4 and Ag3PO4/TiO2 on their photocatalytic activity is evaluated from the photoinduced catalytic, antibacterial, and antifungal performance under visible light irradiation. The photocatalytic activity of pristine and photocorroded Ag3PO4 is increased by similar to 10 times compared to that of pristine and photocorroded Ag3PO4/TiO2. Photocorroded Ag3PO4 and Ag3PO4/TiO2 possess minor antibacterial and antifungal activities (cell survival similar to 90%), whereas using pristine Ag3PO4 and Ag3PO4/TiO2 the cell survival is reduced by 100% after 60 and 120 min, respectively.
Strukturní transformace inkudované viditelným světlem a Cl ionty: vliv na fotokatalytickou, antimicrobiální a antifugální účinnost
Keywords: photocatalysis; antimicrobial; antifungal; photocorrosion; Ag3PO4; TiO2; AgCl; fotokatalýza; antimikrobiální; antifugální; fotokoroze; Ag3PO4; TiO2; AgCl